Assessing Neuro-Systemic & Behavioral Components in the Pathophysiology of Blast-Related Brain Injury - Kobeissy, Firas H.; Mondello, Stefania; Tumer, Nihal; Toklu, Hale Z.; Whidden, Melissa A.; Kirichenko, Nataliya; Zhang, Zhiqun; Prima, Victor; Yassin, Walid; Namas, Chandra; Anagli, John; Svetlov, Stanislav; et al. (Frontiers in Neurology, 2013)
Among the U.S. military personnel, blast injury is among the leading causes of brain injury. During the past decade, it has become apparent that even blast injury as a form of mild traumatic brain injury (mTBI) may lead to multiple different adverse outcomes, such as neuropsychiatric symptoms and long-term cognitive disability. Blast injury is characterized by blast overpressure (BOP), blast duration, and blast impulse. While the blast injuries of a victim close to the explosion will be severe, majority of victims are usually at a distance leading to milder form described as mild blast TBI (mbTBI). A major feature of mbTBI is its complex manifestation occurring in concert at different organ levels involving systemic, cerebral, neuronal and neuropsychiatric responses; some of which are shared with other forms of brain trauma such as acute brain injury and other neuropsychiatric disorders such as PTSD. The pathophysiology of blast injury exposure involves complex cascades of chronic psychological stress, autonomic dysfunction and neuro/systemic inflammation. These factors render blast injury as an arduous challenge in terms of diagnosis and treatment as well as identification of sensitive and specific biomarkers distinguishing mTBI from other non-TBI pathologies and from neuropsychiatric disorders with similar symptoms. This is due to the “distinct” but shared and partially identified biochemical pathways and neuro-histopathological changes that might be linked to behavioral deficits observed. Taken together, this article aims to provide an overview of the current status of the cellular and pathological mechanisms involved in blast overpressure injury and argues for the urgent need to identify potential biomarkers that can hint at the different mechanisms involved.